The Need To Develop Linguistic Competence In Students In Primary School Mother Tongue Classes (Eurasian Scientific Herald, 2022)
The article analyzes the scientific and methodological basis for the introduction of a competency-based approach in the general secondary education system in primary school mother tongue classes. It is based on specific competencies that are formed through the teaching of the mother tongue in secondary schools. The basis of linguistic competence is explained.